أثر الثقافة التنظيمية على أداء الموظفين بمركز علاج وغسيل الكلى ببلدية مصراتة (Journal of Academic Research, 2025)
This study addressed the impact of organizational culture on employee performance at the Kidney Treatment and Dialysis Center in Misurata Municipality. The study aimed to identify the impact of organizational culture on job performance. The research methodology relied on the descriptive approach, which helped to identify the reality of organizational culture and its impact on the level of job performance at the center, analyze it, and reach conclusions that fall within the framework of denying or proving the hypothesis on which the study is based. The comprehensive survey method was used to select the study sample, as it was conducted on the study community, which is represented by all employees at the Kidney Treatment and Dialysis Center in Misurata Municipality, numbering (30) employees. The study concluded that there is a statistically significant impact of organizational culture on employee performance at the Kidney Treatment and Dialysis Center in Misurata Municipality.